Management rizik v procesu zajišťování bezpečnosti české republiky - Paulus, František (Univerzita Pardubice, 2017)
Generally, it is possible to define risk management as coordinated activities to direct and control an organization with regard to risk. Usually, organizations manage risk by identifying it, analysing it and then evaluating whether the risk should be modified by risk treatment to an acceptable level or whether existing measures are sufficient. Same definition and same processing techniques can be used in the area of state administration. However, while assets of organizations are generally denominated in money character, assets within the state administration have the character of protected interests in lives and health of the population, their property and state property and the environment. Czech Republic has responsible approach to ensuring protected interests and applies a policy of risk management at national and regional levels. Resulting tasks are then deal mainly by the integrated rescue system, crisis management bodies and other bodies with territorial responsibility. This paper deals with application of risk management specified in ISO 31000: 2009 in condition of the Czech Republic, namely at the national level and introduces the concrete results of this application.
Risk management in the proces of the Czech Republic security management
Keywords: civil protection; hazard; risk; risk management; Z18; Z19